2010
DOI: 10.1007/s10661-010-1494-4
|View full text |Cite
|
Sign up to set email alerts
|

Determining subsampling effort for the development of a rapid bioassessment protocol using benthic macroinvertebrates in streams of Southeastern Brazil

Abstract: The purpose of this study was to establish a subsampling procedure for benthic macroinvertebrates to aid in the development of a multimetric index to assess the biological condition of streams. Data from six streams that are considered minimally impaired were used. Subsampling was done using a device divided into 24 quadrats. The sediment from each quadrat was sorted, and all organisms were removed and identified. Richness metrics were the most affected by subsample size. Relative-abundance metrics were the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, it is still necessary to test family-level in a biomonitoring program for streams in the whole region, considering there is substantial difference of biota among the biomes. Finally, few studies in Latin America have dealt with developing and testing of other important aspects of biomonitoring protocols, such as sampling procedures and mesh sizes (Buss and Borges 2008), sample size (Schneck and Melo 2010), subsampling methods (Oliveira et al 2011a;Ligeiro et al 2013a), and taxonomic sufficiency (e.g., Melo 2005;Buss and Vitorino 2010).…”
Section: Developing Large-scale Biomonitoring Programs Elsewhere-latimentioning
confidence: 99%
“…However, it is still necessary to test family-level in a biomonitoring program for streams in the whole region, considering there is substantial difference of biota among the biomes. Finally, few studies in Latin America have dealt with developing and testing of other important aspects of biomonitoring protocols, such as sampling procedures and mesh sizes (Buss and Borges 2008), sample size (Schneck and Melo 2010), subsampling methods (Oliveira et al 2011a;Ligeiro et al 2013a), and taxonomic sufficiency (e.g., Melo 2005;Buss and Vitorino 2010).…”
Section: Developing Large-scale Biomonitoring Programs Elsewhere-latimentioning
confidence: 99%
“…Others also have demonstrated that fixed-count size can affect richness estimates (e.g., McCord et al, 2007;Oliveira et al, 2011), the separation between sites or groups (e.g., Cao et al, 2002a;Schneck and Melo, 2010), and performance of MMIs (e.g., Doberstein et al, 2000) and O/E indices (e.g., Nichols et al, 2006;Ostermiller and Hawkins, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All samples were then combined into a single composite sample and preserved with 80% ethanol. In the laboratory, we adopted the subsampling procedure (as tested by Oliveira et al, 2010), which consisted in homogenising the sample on a gridded tray and taking randomly 6 of the 24 quadrats. These six subsamples were fully examined and macroinvertebrates were removed, counted and identified at the lower taxonomic level possible, which was genus-level for all groups but Diptera, Hemiptera and Lepidoptera, which were identified to familylevel.…”
Section: Methodsmentioning
confidence: 99%